Analisis Biaya, Volume, dan Laba Produk Kelapa dalam Meningkatkan Pendapatan Petani: Studi Kasus Desa Totopo, Kecamatan Bilato, Kabupaten Gorontalo - Amelia Moki; Niswatin; Zulkifli Bokiu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the costs, volume and profits (CVL) of coconut products in order to increase farmers' income. Through a CVL analysis approach, this study will identify the break-even point obtained by coconut farmers. This research will also assess production costs and marketing efficiency of coconut products to understand how to increase maximum profits. Thus, it is hoped that the results of this research can provide practical recommendations for coconut farmers to optimize their production and marketing, which will ultimately increase farmers' income and welfare. This research uses a descriptive quantitative approach which aims to describe or describe a condition or phenomenon as it is. In the descriptive approach, researchers do not manipulate or provide certain treatment to the research object. This research was conducted in Totopo Village, Bilato District, Gorontalo Regency. The products that will be analyzed are middleman coconut products, black copra and white copra using data collection techniques by means of documentation, interviews and observation.